Color and image analysis of butterfly beige, butterfly gold and butterfly green dimension rocks exposed to high temperatures. - Bolonini, Thiago Motta [UNESP]; Godoy, Antonio Misson [UNESP]; Figueiredo, Carlos Alberto Machado; Maurício, António; Pereira, Manuel Francisco; Clemente, Igor Magalhães; Silva, Francisco Diones Oliveira (UNESP - Universidade Estadual Paulista, 2017)
The dimension stones are commercially known as Butterfly Beige, Butterfly Gold and Butterfly Green and correspond to quartz syenites with hypersthene that are explored in Barra de São Francisco-Espírito Santo, Brazil. The objective is to analyze the aesthetic effects and to quantify these rocks in the appearance after the exposure to elevated temperatures, from images, colors and petrographic characteristics. The values found for the correlation coefficients (r) between the rocks, already in the first 200ºC, show moderate decharacterizations, being the rocks quite affected by the temperature. Changes caused by thermal cycling combined with moisture accelerate the Fe oxidation process. In addition, by hysteresis, cycling involves the generation of microcracks and the expansion of mineral cleavage planes, as well as overshadowing the contacts between them, facilitating the percolation of fluids (water) and increasing the degree of Fe oxidation while facilitating the diffusion of Fe(OH)2. In view of the obtained results, it is suggested that the studied rocks (mainly the Green variety) be used in indoor coatings and that heat sources, such as the sun, in external coatings, can accelerate the process of color modification in function of the presence of iron-magnesium minerals and, especially, oxidable Fe(OH)2.
Análises de cor e imagem das rochas ornamentais butterfly beige, butterfly gold e butterfly green expostas a altas temperaturas
Keywords: Aesthetic disfiguration; Dimension stones; RGB color standard; Thermal fatigue